SELF-MANAGEMENT IN THE LIGHT OF SĀṀKHYAYOGA (CHAPTER-II) OF ŚRĪMADBHAGAVADGĪTĀ - Pritilaxmi Swain (Veda Jyotih: Jurnal Agama dan Sains, 2024)
Our India is renowned in the globe for its distinctive, rich, glorious heritage and cultural tradition. Ancient India is augmented with unique sacred scriptures like the Vedas, Upanishads, Śrīmadbhagavadgītā, the Rāmāyana, the Mahābhārata, Purāṇas, Bible, Quran, Yoga sῡtras of Patañjali, Dharmaśāstras etc. Amongst these the Śrīmadbhagavadgītā is a marvelous Hindu sacred scripture, which is incorporated in the epic Mahābhārata consisting of 700 verses in 18 chapters in Sanskrit language by Vyasa. The Gītā is the divine discourse spoken by the supreme Lord Krishna himself, so it is told- गीता सुगीता कर्तव्या किमन्यैःशास्त्रसंग्रहैः। या स्वयंपद्मनाभस्य मुखपद्माद्विनिःसृताः।। (महा.भीष्मपर्व, 43.1). It means “The Gītā alone should be sung, heard, recited, studied, taught, pondered, and assimilated properly and well which was emerged directly from the lotus like lips of god Vishnu himself.” Amongst 18 chapters the 2nd chapter is सांख्ययोगः or the yoga of knowledge. Management is an organizational activity to remain the administration disciplined while self-management is an individual activity to keep oneself disciplined. Gītā is full of advises in regard to discipline and regulate the lifestyle of human beings, to be perfect etc., especially the 2nd chapter teaches more about self-regulation, self-management, and self-control. Based on qualitative method, this article tries to ponder about the self management as highlighted in Sāṁkhyayoga of Śrīmadbhagavadgītā. By knowing these one should be well-balanced and mentally sound from internally. Then, one is not affected by these side effects of worldly life by getting knowledge what should be done and what should not be.